Outcome of Triple Negative Breast Cancer(TNBC) as compared to other breast cancers in Bir Hospital, National Academy of Medical Sciences - Joshi, Anip; Chapagain, Sandhya; Shrestha, Sangita; Shakya, Niliza; Luitel, Prajjwol; Rajbhandari, Ishwari; Shrestha, Sujan; Lippey, Jocelyn; Singh, Deependra; Karthikeyan, Prathiksha; Tannock, Ian; Pyke, Christopher (Journal of Society of Surgeons of Nepal, 2024)
Introduction: In Nepal, breast cancer is the second most common cancer accounting for a large number of deaths.The subtype Triple-negative breast cancer (TNBC) is linked to poor prognosis and is characterized by the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2). This study describes the outcome of women with TNBC as compared to other breast cancers in Bir Hospital in Nepal. Methods: This was a cross-sectional study conducted in Bir Hospital, National Academy of Medical Sciences. The breast cancer data in Department of Surgery and Department of Oncology were collected from July 2021 to June 2024. The study data on demographic details, clinical findings, radiological and pathological investigations, operative procedures, neoadjuvant/adjuvant therapy, surgical and oncological outcomeswere collected. The study approval was taken from Institutional Review Board of National Academy of Medical Sciences. Results: There were 72 breast cancer patientsout of which 10 (13.8 %) were TNBC. Majority of the cases (70%) underwent modified radical mastectomy and 60% of them had received neoadjuvant therapy in TNBC cases. One out of 10 had positive margin post mastectomy. The proportion of TNBC patients with postoperative wound infection, seroma and flap necrosis were 10% each. The mean lymph node positivity was less in TNBC group as compared to other breast cancers.There was one recurrence, one metastasis and no mortality till one year follow up. Conclusion: The surgical outcome was satisfactory and with neo-adjuvant, surgery and adjuvant therapy, there is less tumor recurrence and satisfactory disease free survival and overall survival.